Valuation of Accident Reduction - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
The objective of this note is to advise on a desired and workable method that can be used to place values on accident reduction. The first section of this note identifies the need to categorize accidents if accidents are to be valued, and suggests a method of categorization. Following, it identifies the components of cost that make up total accident costs, while further sections suggest methods that can be used to value casualty related costs, and incident related costs. Other Sections discuss how accident valuation may vary between modes, and suggest that accident valuations are consistent with those utilized in other Bank projects (e.g. health projects). Final Sections discuss the manner that accident costs vary with time, and the relationship between the valuation and the accident prediction m model. The final Section summarizes the principal recommendations of the note.